Designs for different futures - Hiesinger, Kathryn B.; Philadelphia Museum of Art; Walker Art Center; Art Institute of Chicago (Philadelphia, PA : Philadelphia Museum of Art ; New Haven : in association with Yale University Press, 2019)
Accessible Worlds : Imagining Disability in Different Futures with Jillian Mercado and Aimi Hamraie / Michelle Millar Fisher -- Can We Fall in Love with Robots? / Emma Yann Zhang -- Variants of Biodesign / Christina Cogdell -- Breakfast before Extinction / Orkan Telhan -- Governance / Marisol LeBron -- Sustainable Development Goals for Earth and Beyond / Danielle Wood -- Mundane Afrofuturist Manifesto / Martine Syms.
"Designs for Different Futures records the concrete ideas and abstract dreams of designers, artists, academics, and scientists engaged in exploring how design might reframe our futures--socially, ethically, and aesthetically. Centered on ninety-nine innovative contemporary design objects, projects, and speculations, this handbook asks readers to contemplate our cultural attitudes toward technology, consumption, beauty, and the social and environmental challenges we face on both a local and global scale in futures near and far. Thought-provoking projects are explored through interpretive texts and interviews by the designers themselves and the core curatorial team. Interspersed with the project pages are newly commissioned texts by academics, scientists, designers, artists, curators, and futurists that explore wide-ranging issues, from historical visions of the future to the use of biological/living materials in products and production processes"--
Designs for Different Futures, Philadelphia Museum of Art, October 22, 2019-March 8, 2020; Walker Art Center, Minneapolis, September 12, 2020-January 3, 2021; The Art Institute of Chicago, February 6-May 16, 2021
boek